Axo‐axonic synapses: Diversity in neural circuit function. Issue 9 (18th December 2020) - Cover, Kara K.; Mathur, Brian N.
Abstract: The chemical synapse is the principal form of contact between neurons of the central nervous system. These synapses are typically configured as presynaptic axon terminations onto postsynaptic dendrites or somata, giving rise to axo‐dendritic and axo‐somatic synapses, respectively. Beyond these common synapse configurations are less‐studied, non‐canonical synapse types that are prevalent throughout the brain and significantly contribute to neural circuit function. Among these are the axo‐axonic synapses, which consist of an axon terminating on another axon or axon terminal. Here, we review evidence for axo‐axonic synapse contributions to neural signaling in the mammalian nervous system and survey functional neural circuit motifs enabled by these synapses. We also detail how recent advances in microscopy, transgenics, and biological sensors may be used to identify and functionally assay axo‐axonic synapses.